2023
DOI: 10.1039/d2sc06403k
|View full text |Cite
|
Sign up to set email alerts
|

Designing strategies and enhancing mechanism for multicomponent high-entropy catalysts

Abstract: High-entropy materials (HEMs) are new-fashioned functional materials in the field of catalysis owing to their large designing space, tunable electronic structure, interesting “cocktail effect”, and entropy stabilization effect. Many effective...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 143 publications
0
14
0
Order By: Relevance
“…After a thorough study, it is revealed that the superb electrocatalytic performance is stemmed from the enlarged ECSA after NH 3 ·H 2 O etching, which can thus expose more catalytically active sites toward the electrooxidation reactions. More significantly, XPS analysis also revealed that the NH 3 ·H 2 O etching can create a higher concentration of high oxidation states of metals, which can serve as active species toward electrooxidation reactions. , Furthermore, the strong synergistic effect evolved from the multielement active sites also contributes to the improved electrocatalytic performance. Upon combination of these advantages, HE-PBA-e can thus deliver superb electrocatalytic performance toward OER, EOR, and UOR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After a thorough study, it is revealed that the superb electrocatalytic performance is stemmed from the enlarged ECSA after NH 3 ·H 2 O etching, which can thus expose more catalytically active sites toward the electrooxidation reactions. More significantly, XPS analysis also revealed that the NH 3 ·H 2 O etching can create a higher concentration of high oxidation states of metals, which can serve as active species toward electrooxidation reactions. , Furthermore, the strong synergistic effect evolved from the multielement active sites also contributes to the improved electrocatalytic performance. Upon combination of these advantages, HE-PBA-e can thus deliver superb electrocatalytic performance toward OER, EOR, and UOR.…”
Section: Resultsmentioning
confidence: 99%
“…More significantly, XPS analysis also revealed that the NH 3 • H 2 O etching can create a higher concentration of high oxidation states of metals, which can serve as active species toward electrooxidation reactions. 41,42 Furthermore, the strong synergistic effect evolved from the multielement active sites also contributes to the improved electrocatalytic performance. 43−52 Upon combination of these advantages, HE-PBA-e can thus deliver superb electrocatalytic performance toward OER, EOR, and UOR.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that HEA catalysts and related materials are promising for use in water-splitting electrodes, and ongoing research is focused on optimizing their properties for this application. [10][11][12][13] HEA catalysts have several advantages over the traditional catalysts used in water-splitting electrodes. First, the multiple metallic elements in the catalyst can work together to enhance the catalytic activity, resulting in a higher reaction rate.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 High-entropy alloys (HEAs) are commonly defined as nearequimolar alloys comprising five or more elements, although slight deviations from this ratio may be tolerated, with each constituent present at concentrations ranging from 5 to 35 at%. [25][26][27] The initial discovery of HEAs was reported in 2004. 28,29 Unlike traditional bimetallic and trimetallic alloys, HEAs typically exhibit exceptional mechanical properties, such as remarkable hardness, enhanced strength, high thermal stability, exceptional wear and fracture resistance, and superior elongation capacity.…”
Section: Introductionmentioning
confidence: 99%